Praxistheorie: Ein soziologisches Forschungsprogramm - Schäfer, Hilmar (transcript, 2016)
Ten years after the »practice turn«: the programmatic constitution of a praxeological theory of motion was received in German sociology and intensively further developed. This book takes provisional stock of the current discussion. In doing so, the practice theory is presented as a research program that sociology has realigned and enriched in theoretical and analytical terms. The contributions highlight different positions within the debate and illustrate the desiderata of practice theory, which arise from conceptual considerations and empirical analyses.